Dal museo alla scuola. I giovani riscoprono la storia dei loro quartieri nelle fotografie di Rodrigo Pais - Furini, Glenda; Sirleto, Francesco (Rivista di studi di fotografia. Journal of Studies in Photography, 2017)
Between January and June 2017, a high school in the suburbs of Rome hosted the exhibition Living in Rome in the Suburbs. Photographs by Rodrigo Pais. Students had an active role in its organization and were in charge of guided tours. Another significant educational aspect was that many of them were either children or grandchildren of people who had lived in the Roman suburbs Pais had recorded between the 1950s and the 1990s, or had direct connections with local residents who had been active in the struggles for housing rights during the same period.